Integrating Digital Technology In Beginner Nahwu Instruction: Development Of Fliphtml5-Based Electronic Teaching Materials Based On Multimedia Learning Theory - Amirul Mukminin; Ruwaida; Shofwatul Fu'adah; Almannah Wassalwa (Cordova Journal, 2026)
Nahwu instruction for beginners remains challenged by static materials and limited digital integration. This study aims to develop FlipHTML5-based electronic instructional material entitled Nahwu lil Mubtadi and to examine its feasibility and students’ responses. Using a Research and Development (R&D) approach, a simplified seven-stage Borg and Gall model was employed, grounded in Richard E. Mayer’s Multimedia Learning Theory. The participants included content experts, media experts, Arabic language experts, and beginner-level students at Madrasah Ibtidaiyah Sukorejo Situbondo. Data were collected through questionnaires, observations, and documentation, and analyzed descriptively using quantitative and qualitative methods. The results indicate that the developed material achieved a highly feasible category based on expert evaluations (88%–91%) and received highly positive student responses (90%). Therefore, the FlipHTML5-based Nahwu lil Mubtadi material is suitable for beginner-level nahwu learning.